Reconstructing Child Protection in the Digital Space: A Comparative Legal Analysis of Indonesia, Australia, and the United States - Diana Tantri Cahyaningsih; Satryo Sasono (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2026)
Digital transformation has enabled children to become active social media users who interact through algorithmic recommendations and account-based features. In Indonesia, age restrictions largely rely on self-declared age, allowing children to access high-risk features, such as direct messaging, group chats, and live streaming, without adequate safeguards. While legal protections for children in digital environments exist, significant gaps remain in the implementation of enforceable standards related to risk classification, age verification, auditability, and compliance measurement. This study aims to evaluate the adequacy of Indonesia’s legal framework on child protection in social media governance, identify regulatory shortcomings, and propose a more operational age-based governance model through a comparative analysis of Australia and the United States. This research employs a doctrinal legal method using statutory, conceptual, and comparative approaches. The analysis focuses on Indonesian regulations governing child protection, electronic systems, and personal data protection, as well as Australia’s Social Media Minimum Age framework and the United States’ Children’s Online Privacy Protection Act (COPPA). The findings reveal that Indonesia’s primary regulatory weakness lies in the absence of technical standards linking legal obligations to measurable compliance mechanisms. Existing regulations provide broad protection mandates but offer limited guidance on platform accountability and risk-based feature governance. In response, this study proposes a two-tier age governance model that differentiates protections for younger children and adolescents, integrates privacy-preserving age-verification mechanisms, and combines co-regulatory oversight with digital citizenship education. The proposed framework offers practical guidance for developing technical audit standards, strengthening platform accountability, and enhancing the protection of children’s rights within Indonesia’s evolving digital ecosystem.